Mathematical Modeling and Simulation with MATLAB - Lee, Sheldon; Buzby, Megan (Open textbook library., 2021)
This textbook attempts to provide you with an overview of the commonly used basic mathematical models, as well as a wide range of applications. It offers a perspective that brings you back to the modeling process and the assumptions that go into it.